Informal Elementary Science: Repertoires of Parental Support - Katherine Short-Meyerson; Susannah Sandrin; Margarita Jimenez-Silva (MDPI AG, 2024)
Children's early exposure and participation with science activities may help reduce underrepresentation issues that are often seen later in some disciplines of science, technology, engineering, and mathematics (STEM) majors and occupations. To help understand these trends, this study investigated the repertoire of parental support during hands-on science activities with their children with regards to ethnicity (Latiné families of predominantly Mexican origin and non-Latiné, primarily White, families) and gender. It was informed by work that examines gender, race, and ethnicity differences in STEM participation. Participants were 153 girls and boys, aged 8 to 12 years, and their mothers and fathers in the Southwestern United States. Each parent-child dyad's behaviors during hands-on science activities together were examined. After controlling for family annual income and parental level of education, there were several variations by ethnicity and gender in parents' support of their children (e.g., help and encouragement), children's exploration of the activities, children's talkativeness, and the amount of time they engaged in the activities. Suggestions for expanding STEM education programs to be more inclusive of underrepresented communities are discussed.